The Role of Acid Catalysts in Optimizing Iron Adsorption: Mechanistic Insights and Applications - Resi, Nadyn Amalia; Ichwan, Muhammad Maulana; Hapsari, Fatimah (Vocational College of Universitas Diponegoro, 2024)
This research aims to evaluate the influence of acid catalysts HCl and H2SO4, on the adsorption efficiency of Fe (Iron) using silica extracted from rice husk ash. The synthesis process employs the sol-gel method, including the initial treatment of rice husk ash, sodium silicate extraction, and the formation of silica gel with acid catalysts. The research results show that acid catalysts affect the structure and adsorption efficiency, with the highest efficiency obtained using 0.5M HCl catalyst with an adsorption efficiency of 62.3% and 0.5M H2SO4 catalyst with an adsorption efficiency of 24.85%. FTIR analysis to identify functional groups revealed siloxane (Si-O-Si) and silanol (Si-OH) contain on silica, which support the metal adsorption capability. The results of the morphological observation using SEM show that the amorphous silica structure has diverse pores based on the type of catalyst.